Deteksi Objek Di Jalan Tanpa Penerangan Pada Kendaraan Menggunakan White Dan Yellow Headlamp - Rahmat Ahmad; I Wayan Yudi Martha Wiguna; Anggun Prima Gilang Rupaka; Handoko Handoko (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2025)
Road conditions without lighting often pose a high risk of traffic accidents, especially in rural areas or on alternative routes. This study aims to analyze the effectiveness of using white and yellow headlamps on vehicles in detecting objects under dark road conditions. The methods employed were field experiments and interviews with drivers. The results show that the use of white headlamps, based on SWOT analysis, is positioned in Quadrant I at the coordinates 0.92 and 0.23, while the use of yellow headlamps, based on SWOT analysis, is positioned in Quadrant I at the coordinates 0.47 and 0.08. These findings indicate that the use of white headlamps is still superior to yellow headlamps under nighttime conditions, although the difference is not highly significant on roads without lighting